1964
DOI: 10.1139/y64-023
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Stimulation and Forearm Blood Flow

Abstract: Forty-six adult male subjects have been exposed to strong vestibular stimulation produced by controlled cyclic nodding of the head while being rotated in the horizontal plane on a turntable at constant angular velocity. Forearm blood flow was measured with a mercury-in-rubber strain gauge plethysmograph standardized against a conventional plethysmographic technique. There was wide variability among the subjects in the amount of vestibular stimulation needed to cause nausea just short of emesis. Motion sickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1974
1974
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 1 publication
0
4
1
Order By: Relevance
“…Ablation of both nodulus and uvula abolished the kinetosic syndrome (Tyler & Bard, 1949;Wang & Chinn, 1956). However, although several autonomic functions are altered in motion sickness, an appreciable modification of blood pressure and heart rate has never been reported in either animals or man (Tyler & Bard, 1949;Sunahara, Johnson & Taylor, 1964). This is in contrast with our report of marked effects on cardiovascular variables following stimulation of the uvula (Bradley et al 1987a).…”
Section: Anatomical Observationscontrasting
confidence: 99%
“…Ablation of both nodulus and uvula abolished the kinetosic syndrome (Tyler & Bard, 1949;Wang & Chinn, 1956). However, although several autonomic functions are altered in motion sickness, an appreciable modification of blood pressure and heart rate has never been reported in either animals or man (Tyler & Bard, 1949;Sunahara, Johnson & Taylor, 1964). This is in contrast with our report of marked effects on cardiovascular variables following stimulation of the uvula (Bradley et al 1987a).…”
Section: Anatomical Observationscontrasting
confidence: 99%
“…The most evident of these responses are cold-sweating (Cheung et al, 2011; Hemingway, 1944; Nobel et al, 2012; Sclocco et al, 2015), changes in cutaneous thermoregulatory vascular tone (Nalivaiko et al, 2015), and pallor (Cassano et al, 1989; Kolev et al, 1997). Changes in skin blood flow that result in pallor are not accompanied by alterations in blood pressure (Sunahara et al, 1987; Sunahara et al, 1964), showing that they are not due to a global increase in sympathetic nervous system activity. In fact, there is evidence of increased blood flow to muscle and decreased blood flow to the skin during motion sickness (Cheung et al, 2001).…”
Section: Prodromal Physiological Changes: Potential Physiological mentioning
confidence: 99%
“…The first study where skin blood flow was assessed during MS provocation, reported a 50-60% fall in finger pulse volume indicative of vasoconstriction 7 . Several other early studies demonstrated that MS is associated with an increase in forearm blood flow 35,36 . However, they were conducted by means of venous occlusion plethysmography (a method based on the volume changes in the forearm), and thus could not determine whether blood flow increased in the skin or in the muscles of the forearm.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Several other early studies demonstrated that MS is associated with an increase in forearm blood flow. 35,36 However, they were conducted by means of venous occlusion plethysmography (a method based on the volume changes in the forearm), and thus could not determine whether blood flow increased in the skin or in the muscles of the forearm. Using the difference between forearm and finger temperature as a surrogate measure of cutaneous vascular tone, Nobel and colleagues concluded that MS attenuates cutaneous vasoconstriction provoked by immersion in the cold water.…”
Section: Introductionmentioning
confidence: 99%